The perceived insufficient milk supply and nipple trauma among breastfeeding mothers - Rizqa Ainuni'mah; Kismi Mubarokah (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Karangasem Public Health Center has the lowest coverage in Pemalang Regency, about 9.9 percent, or only 79 babies who get exclusive breast milk from a total of 798 babies. This is still far from the target of 60 percent. A total of 17 out of 20 mothers who have babies aged 6-12 months do not exclusively breastfeed.  Purpose: To analyze factors (characteristics, knowledge, perceptions) related to exclusive breastfeeding behavior.Method: The cross-sectional research design was applied to 86 respondents selected by simple random sampling using instruments tested for validity and reliability. Chi-square and Fisher exact tests were used for bivariate analysis (CI 95 percent).Results: Respondents between 20-40 years of age, a low education level (58.1 percent), non-working (81.4 percent), multipara (68.6 percent), sufficient knowledge (57 percent), and perception of lack of support towards exclusive breastfeeding (53.5 percent) and they do not provide exclusive breast milk (73.3 percent). There is a relationship between education (p:0.008), parity (p:0.027), knowledge (p:0.001), and perception (p:0.001) with the practice of exclusive breastfeeding. While age (p:0.533) and working status (p:0.541) are not related to exclusive breastfeeding practices.Conclusion: Innovation of Maternal and Child Health programs in Health Centers related to increasing exclusive breast milk coverage needs to be done, especially on breastfeeding benefits and techniques.